Experimental investigation for the detection of high-risk external electrical faults through stator current analysis. Issue 2 (3rd April 2019) - Haouem, Nassim Eddine; Bouras, Slimane; Bouras, Abdelkarim; Rouabhia, Chems Eddine
ABSTRACT: Induction motors may be subject to external electrical faults, of which the consequences are highly critical and dangerous. If the electromagnetic shielding does not intervene in time, the windings will be damaged due to an intense rise in stator current and therefore this actuator will be out of service. Multiple analysis approaches of Park's current vector components (FFT, STFF, Park Orbit, Hilbert-Park and Mean Square Spectrum) discussed in our paper are illustrated for the detection of the absence of one of the power phases during the operation of the induction motor and the errors of its connection to the electrical network on an experimental bench dedicated to the diagnosis. The results obtained by applying this fairly simple methodology allow to monitor the induction motor during its proper functioning and to make a reliable assessment of the cause and the facts if there is an incident due to these external electrical faults.